Sir William Cornwallis the Younger (c.1579-1614) and the emergence of the essay in England - Butler, S; Sophie Perdita Butler (2013)
This thesis provides a full-length critical treatment of the Essayes (1600-01) of Sir William Cornwallis (c.1579-1614). Cornwallis' Essayes are the first examples of the ‘familiar’ essay in English: to which the rhetorical shaping of persona and the use of the personal voice are central. This is the first such study of Cornwallis since the first half of the twentieth century, and situates his Essayes within their cultural, social, and material contexts. The thesis draws upon previous work on Cornwallis and his Essayes from the 1930s and 1940s, but also on recent developments in early-modern English studies, especially in the fields of the history of rhetoric and the history of reading. The thesis challenges the assumptions behind two major critical approaches to the early-modern essay: firstly that it is a form in which the personal voice can be unambiguously expressed, and secondly that it is an essentially unoriginal genre which is more closely related to reading than to writing. This thesis qualifies these approaches, while demonstrating that the origins of each are found in the rhetorical practices of early English essays. This thesis argues however that Cornwallis’s essays are elaborate fusions of classical commonplaces, humanistic rhetoric, and ethical theories of how to live, resulting from complex interactions between different strands of humanistic educative practices, and that Cornwallis’s use of the personal voice is shaped by ethically-inflected rhetorical theories of affect and imitation. The thesis further attempts to think about how essays were being read in this period, and to do so offers a study of the material traces of reading, in the form of annotations and commonplace books, left by early-modern readers of John Florio’s English translation of Montaigne (1603).